Earning Per Share Under International Accounting Regulations and Based on the Example of Companies Listed on the Warsaw Stock Exchange - Prewysz-Kwinto, Piotr; Voss, Grażyna (European Journal of Economics and Business Studies, 2017)
Earnings per share is one of the most important financial ratios facilitating investors make decisions about the choice of a company to invest in. To fulfill this role, it should be calculated according to the same rules by all companies, so that the results can be compared correctly. Therefore, the IASB (International Accounting Standards Board) issued a special standard comprehensively regulating the rules of its calculation and presentation in financial statement. It is International Accounting Standard 33 – Earning per share, which was released in December 2003. It was first applied to financial statements prepared for the reporting period starting after January 1, 2005. The standard was revised once – in 2008. This standard requires calculation and presentation in financial statement basic and diluted earnings per share and accurately specifies how to do it. The aim of this paper is to describe the rules of calculating, presenting and disclosure information about earning per share under IAS 33 as well as to analyze the presentation of such information in financial statements of the largest companies listed on the Warsaw Stock Exchange. The main methods used include the analysis and evaluation of legal acts and subject-related literature as well as the analysis of information disclosed in financial statements of the largest companies listed on the Warsaw Stock Exchange.